CLINICAL AND IMMUNOLOGICAL PARAMETERS IN EARLY RHEUMATOID ARTHRITIS - V. V. Sokolova (SPb RAACI, 2014)
Abstract. Early events in rheumatoid arthritis (RA) play a main role in development and progression of immunocomplex-associated inflammation. Early diagnostics of RА allows adequate immunosuppressive medications to stop the disease progression, to obtain more significant clinical effect and improve prognosis of the disease. We examined 85 patients with early RА (less than 1 year from the onset of disease), as well as thirty patients with long-lasting RA. Twenty-six age- and sexmatched healthy donors served as a control group. Standard clinical examination was performed. In all RA patients we measured concentrations of antifilagrine antibodies (AFA) including antikeratin antibodies, antiperinuclear factor, antibodies to cyclic citrullinated peptide and serum levels of main cytokines, i.e., IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, as well as TNFα, VEGF, IFNγ, МСР-1.Rheumatoid factor (RF) was detectable in 44% patients with early RA, AFA, in 62% cases. These parameters in patients with long-lasting RA were 88% and 57% accordingly. Positive AFA were found in patients with higher expression of clinical and laboratory markers.The levels of proinflammatory cytokines such as IL-1β, IL-6 and chemokine MCP-1 were significantly elevated in patients with early and long-lasting RA in comparison with control group, but patients with longlasting RА showed the highest MCP-1 levels. The associations between severity markers of RA and serum levels of cytokines were demonstrated.Our data support important diagnostic role of АFА at the early stages of RА. Serum cytokine concentrations can be used as additional laboratory and prognostic criteria of RA.